Cardiovascular diseases and apical periodontitis: association not always implies causality - Jiménez-Sánchez, María Carmen (Med Oral Patol Oral Cir Bucal, 2020)
BACKGROUND: Several studies published in the last two decades have found an association between the prevalence of apical periodontitis (AP) or root canal treatment (RCT) and cardiovascular diseases (CVDs). However, the demonstration of association does not prove by itself the existence of a cause–effect relationship. Two diseases can appear as statistically related without any of them directly affecting the values of the other, resulting in a non-causal relationship. The aim of this narrative review is to summarize the current state of knowledge regarding the association between AP and CVDs, analysing it according to the Hill's causality criteria. MATERIAL AND METHODS: Epidemiological studies carried out on the association between CVDs and AP or RCT published in English until 8 December 2019 were identified. Forty-four articles were selected and its results were analysed. RESULTS: Numerous cross-sectional epidemiological studies have found significant relationship between CVDs and AP. The odds ratio values range 1.6 - 5.4. However, other studies have not found significant association. Respect to RCT, some studies found correlation, but others found no association or even found that RCT is a protective factor against CVDs. CONCLUSIONS: The results are inconsistent and a causal relationship between CVDS and endodontic disease cannot be stablished. The risk factors common to both diseases can act as confounding factors, biasing the results. To reach definitive conclusions about the type of association (causal or non-causal) between both diseases, longitudinal epidemiological studies must be carried out to establish the temporal relationship and the dose-response gradient. Key words:Apical periodontitis, atherosclerosis, cardiovascular disease, coronary heart disease, endodontic medicine, root canal treatment.